Konsep Mura Dalam Anime Kasajizou - Zaki Ainul Fadli (KIRYOKU, 2019)
(Title: “Mura ” Concept in Kasajizou Anime) This article aims to uncover the concept of mura in the Kasajizou anime. Mura is one of the traditional Japanese systems, besides ie and kuni. The research method used is the literary sociology approach, namely by revealing one of the anime’s structures (mura ’background) in the anime and relating it to "mura " as a territorial concept in Japanese tradition according to Inagaki's explanation. The results showed that "mura " in the fairy tale anime Kasajizou was similar to the concept of mura which was presented by Inagaki, which is a local organization for the purpose of production and as a community formed naturally for the god who protected the area. In conclusion, the concept of mura in the fairytale anime confirms Inagaki's exposure of mura as one of the elements in the traditional system of Japanese society.